IMMATURE PLATELET FRACTION EXAMINATION IN IMMUNE THROMBOCYTOPENIC PURPURA - Atika Indah Sari (Sean Institute, 2023)
Introduction: Immune Thrombocytopenic Purpura is an abnormality of decreased platelets caused by the destruction of platelets which is mediated by the immune and usually occurs in young adult women. The clinical manifestations are mild bleeding in the skin, such as petechiae, ecchymosis, and intracranial hemorrhage. IPF could help clinicians in diagnosing ITP. Case report: It had been reported a 22-year-old female patient who has diagnosed with thrombocytopenia et causa Immune Thrombocytopenia Purpura and moderate anemia et causa acute bleeding and treated with corticosteroid. Conclusion: IPF could help in diagnosing ITP.